Introduction to the Special Issue on Gender Studies - Fomin, Vladislav V.; Grigas, Vincas (Information & Media, 2023)
This paper provides an introduction to the special issue on gender studies. It surveys each paper and identifies commonalities and dissimilarities among them, as well as suggests the potential readership for the papers based on the problems addressed and the findings. Prof. Natalija Mažeikienė from Vytautas Magnus University served as the guest editor of the special issue.